Skin manifestations of inborn errors of NF-κB - Shen, Yitong; Boulton, Anne P. R.; Yellon, Robert L.; Cook, Matthew C. (Frontiers in Pediatrics, 2023)
More than 400 single gene defects have been identified as inborn errors of immunity, including many arising from genes encoding proteins that affect NF-B activity. We summarise the skin phenotypes in this subset of disorders and provide an overview of pathogenic mechanisms. NF-B acts cell-intrinsically in basal epithelial cells during differentiation of skin appendages, influences keratinocyte proliferation and survival, and both responses to and amplification of inflammation, particularly TNF. Skin phenotypes include ectodermal dysplasia, reduction and hyperproliferation of keratinocytes, and aberrant recruitment of inflammatory cells, which often occur in combination. Phenotypes conferred by these rare monogenic syndromes often resemble those observed with more common defects. This includes oral and perineal ulceration and pustular skin disease as occurs with Behcet’s disease, hyperkeratosis with microabscess formation similar to psoriasis, and atopic dermatitis. Thus, these genotype-phenotype relations provide diagnostic clues for this subset of IEIs, and also provide insights into mechanisms of more common forms of skin disease.